Penggunaan media komunikasi android apps dalam optimalisasi pengawas minum obat (PMO) terhadap tingkat kepatuhan dan kesembuhan penderita tuberkulosis paru - Rita Dwi Pratiwi; Dewi Fitriani; Betty Betty (Holistik Jurnal Kesehatan, 2021)
DOTS (Directly Observed Treatment Short-Course) via android apps for promoting adherence to tuberculosis management among pulmonary tuberculosis patients  Background: Pulmonary tuberculosis is a global health problem that has become a global concern for the last two decades. Indonesia occupies the second largest position of TB cases after India, which is equal to 10. The prevalence of pulmonary TB in Banten Province is 315 / 100,000 population, where the area with the highest prevalence in South Tangerang City, which is 1,691/100,000 of population. In this global era, mobile phones are very close to society. It is because they can access information messages via electronic media such as cell phones so that they can change a person's behavior, especially health behavior. There are many opinions that the health sector has got a significant benefit from this transformation..Purpose: To identify the effectiveness of DOTS (Directly Observed Treatment Short-Course) via android apps for promoting adherence to tuberculosis management among pulmonary tuberculosis patients in Pamulang Public Health Centre, South Tangerang City.Method: A quantitative research with the design method of quasi-experiment. The population was all patients with pulmonary tuberculosis in the Pamulang Public Health Centre, South Tangerang City. The sample taken by an accidental purposive sampling technique, got of 40 participants divided in two groups and comprising 20 participants in the control group and 20 participants in the experimental groupResults: Showing that there was uncorrelated between age, gender, and weight with the level of obedience and recovery in both the control and experimental groups. There was a significant correlation between the patient's medication obedience level and the recovery rate for pulmonary TB patients in 2 groups. Besides, there was a significant difference between obedience in the control group and the experimental group, with a p-value of 0.04. There was a significant difference between recovery in the control group and the experimental group with a p-value of 0.019Keywords : DOTS (Directly Observed Treatment Short-Course); Android apps; Promoting adherence; Tuberculosis management; Pulmonary; Patients Pendahuluan: Tuberkulosis paru merupakan permasalahan kesehatan global yang menjadi perhatian dunia selama dua dekade terakhir. Indonesia menempati posisi terbesar kedua kasus TB setelah India yaitu sebesar 10Prevalensi TB paru di Provinsi Banten sebesar 315/100.000 penduduk dimana wilayah dengan prevalensi paling tinggi adalah Kota tangerang Selatan yakni sebesar 1.691 per100.000 penduduk. Pada era global ini telepon genggam sangat dekat dengan masyarakat. Hal ini dikarenakan pesan informasi bisa diakses melalui media elektronik seperti telepon genggam sehingga bisa merubah perilaku seseorang khususnya perilaku kesehatan. Ada banyak pendapat bahwa sektor kesehatan sangat diuntungkan oleh transformasi ini.Tujuan: mengidentifikasi efektifitas penggunaan Media Komunikasi Telepon dalam Optimalisasi PMO Terhadap Tingkat Kepatuhan dan Kesembuhan Penderita TB Paru Di Wilayah Puskesmas Pamulang Tangerang Selatan.Metode: Penelitian ini Quasi Experiment 2 group. Populasi penelitian yaitu Seluruh pasien pasien TB Paru di Wilayah Puskesmas Pamulang Kota Tangerang Selatan dengan tehnik Sampling Purposive Sampling dan sesuai dengan jumlah pasien yang ada saat itu.Hasil: menunjukkan tidak ada hubungan antara Umur, Jenis kelamin dan Berat badan dengan tingkat kepatuhan maupun kesembuhan baik pada kelompok kontrol maupun kelompok eksperiment, terdapat hubungan yang signifikan antara tingkat kepatuhan minum obat pasien dengan tingkat kesembuhan penderita TB paru pada 2 grup. Serta perbedaan yang signifikan antara kepatuhan pada kelompok kontrol dan kelompok eksperimen dengan p value 0.04 serta ada perbedaan yang signifikan antara kesembuhan pada kelompok kontrol dan kelompok eksperimen dengan p value 0.019.